Capabilities of the GAMMA-400 gamma-ray telescope to detect gamma-ray bursts from lateral directions. Issue 1 (1st January 2022) - Leonov, A.A.; Galper, A.M.; Topchiev, N.P.; Arkhangelskaja, I.V.; Arkhangelskiy, A.I.; Bakaldin, A.V.; Chernysheva, I.V.; Dalkarov, O.D.; Egorov, A.E.; Kheymits, M.D.; Korotkov, M.G.; Malinin, A.G.; et al.
Highlights: The GAMMA-400 gamma-ray telescope performance for lateral aperture. Detection of GRB from the lateral aperture in the energy range from ∼ 10 to ∼ 100 MeV. The problem of connection between high- and low-energy gamma-ray emissions of GRBs. Abstract: The currently developing space-based gamma-ray telescope GAMMA-400 will measure the gamma-ray and electron + positron fluxes using the main top-down aperture in the energy range from ∼ 20 MeV to several TeV in a highly elliptic orbit (without shading the telescope by the Earth and outside the radiation belts) continuously for a long time. The instrument will provide fundamentally new data on discrete gamma-ray sources, gamma-ray bursts (GRBs), sources and propagation of Galactic cosmic rays and signatures of dark matter due to its unique angular and energy resolutions in the wide energy range. The gamma-ray telescope consists of the anticoincidence system (AC), the converter-tracker (C), the time-of-flight system (S1 and S2), the position-sensitive and electromagnetic calorimeters (CC1 and CC2), scintillation detectors (S3 and S4) located above and behind the CC2 calorimeter and lateral detectors (LD) located around the CC2 calorimeter. In this paper, the capabilities of the GAMMA-400 gamma-ray telescope to measure fluxes of GRBs from lateral directions of CC2 are analyzed using Monte-Carlo simulations. The analysis is based on off-line second-level trigger construction using signals from S3, CC2, S4 and LD detectors. For checking the numerical algorithm the data from space-based GBM and LAT instruments of the Fermi experiment are used, namely, three long bursts: GRB 080916C, GRB 090902B, GRB 090926A and one short burst GRB 090510A. The obtained results allow us to conclude that from lateral directions the GAMMA-400 space-based gamma-ray telescope will reliably measure the spectra of bright GRBs in the energy range from ∼ 10 to ∼ 100 MeV with the on-axis effective area of about 0.13 m 2 for each of the four sides of CC2 and total field of view of about 6 sr.